2017
DOI: 10.1186/s40104-017-0155-7
|View full text |Cite
|
Sign up to set email alerts
|

New approach to assess sperm DNA fragmentation dynamics: Fine-tuning mathematical models

Abstract: BackgroundSperm DNA fragmentation (sDF) has been proved to be an important parameter in order to predict in vitro the potential fertility of a semen sample. Colloid centrifugation could be a suitable technique to select those donkey sperm more resistant to DNA fragmentation after thawing. Previous studies have shown that to elucidate the latent damage of the DNA molecule, sDF should be assessed dynamically, where the rate of fragmentation between treatments indicates how resistant the DNA is to iatrogenic dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Sperm DNA fragmentation analysis was performed for each sample after 0, 6 and 24 hr of cooled storage. SDF values were then analysed using three mathematical regression models for dynamic assessment: linear, exponential and second order polynomial, as previously described (Ortiz et al, ). In order to compare which model was the better fit for SDF, the coefficient of determination ( R 2 ) was calculated.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sperm DNA fragmentation analysis was performed for each sample after 0, 6 and 24 hr of cooled storage. SDF values were then analysed using three mathematical regression models for dynamic assessment: linear, exponential and second order polynomial, as previously described (Ortiz et al, ). In order to compare which model was the better fit for SDF, the coefficient of determination ( R 2 ) was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…It is also well known that stallion semen cooling affects routine sperm quality parameters and pregnancy rates (Brinkerhoff et al, ; Foster et al, ; Heckenbichler, Deichsel, Peters, & Aurich, ; Henderson, Capewell, & Johnson, ; Kiser et al, ; Love et al, ; Urbano et al, ), mostly attributable to the relatively short longevity of cooled‐stored semen of approximately 24–48 hr. Other studies have shown that semen cooling increases SDF values after 48 hr of storage (Blottner et al, ; Fraser, Strzezek, & Kordan, ; Gil et al, ; Linfor & Meyers, ; Love & Kenney, ; Love et al, ; Ortiz et al, ).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations